Penerapan Kompres Hangat dalam Menurunkan Nyeri Panggul pada Pasien CA Cervix di Ruang Wijaya Kusuma RSUD Prof. Dr. Margono Soekarjo - Jauhar Nudin; Ikit Netra Wirakhmi (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2026)
Cervical cancer is the second most common cancer in Indonesia and often causes pelvic pain due to tumor infiltration and pressure on surrounding tissues. This pain can significantly affect patients’ comfort, mobility, sleep quality, and overall quality of life, making effective pain management an essential component of nursing care. Objective: This study aims to describe nursing care and evaluate the effectiveness of warm compress therapy in reducing pelvic pain in Mrs. J with cervical cancer. Methods: A descriptive study was conducted using a nursing care process case study approach, including assessment, diagnosis, planning, implementation, and evaluation. The intervention was carried out over three consecutive days (January 19–21, 2026) at Prof. Dr. Margono Soekarjo Hospital. Results: Prior to the intervention, the patient reported pelvic pain at a scale of 7, appeared grimacing, and demonstrated protective behavior. Following routine warm compress application, the pain scale decreased significantly to 2–3 (mild pain), the patient appeared more relaxed, and protective behavior diminished. Conclusion: Warm compress therapy is effective as a complementary non-pharmacological intervention for reducing pelvic pain intensity and improving comfort in cervical cancer patients.